DFT study of the reaction mechanism of CuO–char in chemical-looping combustion. Issue 23 (31st October 2021) - Zhao, Deng; Liu, Hui; Zhu, Di; Wang, Huashan; Lu, Pengcheng; Qin, Ming
Abstract : In the CuO–char mechanism of chemical-looping combustion, direct solid–solid reaction is more favorable than oxygen decoupling. Abstract : Understanding the reaction mechanism of CuO and char is crucial for developing chemical looping combustion of carbon-containing solid fuels. Density functional theory is used to study the chemical looping combustion mechanism of CuO. The three reaction processes of Cu4 O4 cluster oxygen release, O2 -char, and Cu4 O4 cluster-char are described in detail. The energies of paths are compared and verify that the solid–solid direct reaction mechanism between CuO and char is more favorable than the oxygen uncoupling mechanism, and this proves the results of previous experiments. The best possible reaction path for the solid–solid direct reaction is proposed. The agglomerated dioxygen and char form unstable intermediates; this increases the energy span of the reaction path and hinders the oxidation process of char. Cu can easily dissociate O2 into singlet oxygen and transfer this oxygen to char in a lower energy single oxygen transfer mode to form a CO2 precursor. This may be the essence of the catalytic effect of Cu in the chemical looping combustion reaction. The solid–solid direct reaction mechanism and the catalysis of metals should receive more attention in chemical looping combustion.